What Christ thinks of the church Revelation 1-3 expounded - Stott, John Robert Walmsley, 1921- (Milton Keynes, UK Word, 1990)
Includes photigraphs.
Keywords: Bible. N.T. Revelation I-III -- criticism, interpretation, etc